FUSOGENIC LIPOSOME FOR THE TREATMENT OF FUNGAL MENINGITIS: AN OVERVIEW - Susan Alex, Irene; Jose, Jeneetta; R, Rahul; Gopal, Anju; Priya, Anu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Fungal meningitis is an infection which is caused by fungus which spreads through the blood to the spinal cord. People with weakened immunity get this disease easily like persons with AIDs, etc. To make sure the disease is fungal meningitis, a sample is taken from the cerebrospinal fluid and it is sent to the laboratory. Usually, fungal meningitis is not mediated from person to person, but it is caused when a fungi are inhaled from the surrounding and spread into the blood to the central nervous system. Normally medications such as vaccines, IV, and oral suspensions are given to the people for curing fungal meningitis. Commonly used drugs are Amphotericin B and fluconazole oral suspension. Amphotericin B is an antifungal, antiprotozoal, and hydrophobic drug. However, these drugs cannot give a directly as medication therapy for the patients, because it offers toxic effect and side effects, absorption rate is slower, and crossing the blood–brain barrier (BBB) is getting difficult. Adverse effects can be minimized with the application of nanotechnology. Therefore, in human medical services, the availability of molecular nanotechnology will provide rapid progress. Nanoparticle (NP) systems help to improve the solubility of poorly water-soluble drugs which has been explained using Noyes–Whitney equations. Nanoparticles offers several advantages as a drug delivery system, such as better drug bioavailability, reduction of dosing frequency enables them for the betterment of diseases, can cross the BBB, and it is very cost-effective. Types of NP include polymeric NP, carbon nanotubes, metallic structures, nanocrystals, and fusogenic liposomes. Fusogenic liposomes are a peculiar class of phospholipid vesicles. The fusogenic liposomes can deliver encapsulated NP into the targeted sites and also can cross the BBB. On comparing with cationic liposomes, fusogenic liposomes are more effective as well as rapid in the drug delivery.